Sizing of Energy Storage Systems in Electric Vehicles based on Battery-Supercapacitor Technology - Alfani, Denny; Adityanugraha, Dimas Febry; Putri, Vita Lystianingrum Budiharto; Pamuji, Feby Agung (Department of Electrical Engineering ITS and FORTEI, 2024)
The purpose of this research is to determine the ideal hybrid energy storage system (HESS) size with the goal to improve the effectiveness and efficiency of combined battery and supercapacitor energy storage in electric vehicles. The research uses Mixed Integer Linear Programming (MILP) to determine the most suitable configurations using simulation data from a modeled electric vehicle. The results show that MILP works at identifying the specific capacity needs of the storage system, which change based on the vehicle's power and energy capacity. The innovation provides a paradigm for the development of sustainable and highly efficient electric vehicles in the future, while also enhancing the functionality of current electric vehicles.